Evaluasi Penerapan Keselamatan dan Kesehatan Kerja Bekerja di Ketinggian pada Konstruksi Bangunan Gedung - Rahmatullah, Rahmatullah; Andri, Andri; Umurani, Khairul; Fathimah, Hafizah Siti; Hafiz, Muhammad (Universitas Batanghari Jambi, 2025)
Building construction work is one of the sectors with a high risk of work accidents, especially in activities at height. This risk is influenced by project dynamics, limited workforce experience, work environment conditions, and weak implementation of occupational safety and health (K3) management. This study aims to identify the main problems in construction work at height and evaluate the implementation of applicable K3 regulations, standards, methods, and techniques. The focus of the study is directed at the consistent application of K3 Construction methods and regulations at the stages of implementing lower structure, basement, architecture, upper structure, mechanical, electrical, plumbing (MEP) to testing and specifically for upper structure and MEP work, K3 Construction methods and regulations and K3 working at height are applied. The research method used is evaluative-qualitative with field observation and document analysis, followed by integrated application of K3 procedures on the projects studied. The results of the study after the joint application, references, standard procedures, regulations, K3 construction methods and K3 working at height that are consistent in the construction projects that have been observed, it is concluded that the method has been able to significantly minimize work accidents in the workplace.